PELAYANAN SIRKULASI MENGGUNAKAN APLIKASI SENAYAN DI UNIT PELAKSANA TEKNIS PERPUSTAKAAN UNIVERSITAS TANJUNGPURA - Enny Mujiati E.21109005 (FISIP Universitas Tanjungpura, 2013)
This paper writing slated to give grasp about application senayan at bibliographic Technical Executor Unit Tanjungpura University. About problem of service utilize senayan application at circulation that happening bibliographic enough pulls to be analyzed remembers is still a lot of the about problems which can't yet most solve. Via this paper writing also been meant, that remedial process goes on to be done, so user bibliographic as gets to utilize comfortable ala library. Senayan application at bibliographic Technical Executor Unit Tanjungpura University. Range 5 (five) thing which is support of physical facility aspect, support of aspect to mainstay, support of aspect to comment, support of surety aspect, and support of empathy aspect so thus get clearly been known support which is required, and condition of aught library now. Keywords: Service, Senayan application, User Bibliographic and Circulation.